Progress in enrichment of n-3 polyunsaturated fatty acid: a review - Xie, Dan; Chen, Ye; Yu, Junwen; Yang, Zhuangzhuang; Wang, Xiaosan; Wang, Xingguo (Critical reviews in food science and nutrition, 2023)
n-3 Polyunsaturated fatty acids (n-3 PUFA) has been widely used in foods, and pharmaceutical products due to its beneficial effects. The content of n-3 PUFA in natural oils is usually low, which decreases its added value. Thus, there is an increasing demand on the market for n-3 PUFA concentrates. This review firstly introduces the differences in bioavailability and oxidative stability between different types of PUFA concentrate (free fatty acid, ethyl ester and acylglycerol), and then provides a comprehensive discussion of different methods for enrichment of lipids with n-3 PUFA including physical-chemical methods and enzymatic methods. Lipases used for catalyzing esterification, transesterification and hydrolysis reactions play an important role in the production of highly enriched various types of n-3 PUFA concentrates. Lipase-catalyzed alcoholysis or hydrolysis reactions are the mostly employed method to prepare high-quality n-3 PUFA of structural acylglycerols. Although many important advantages offered by lipases in enrichment of n-3 PUFA, the high cost of enzyme limits its industrial-scale production. Further research should focus on looking for biological enzymes with extraordinary catalytic ability and clear selectivity. Other novel technologies such as protein engineering and immobilization may be needed to modify lipases to improve its selectivity, catalytic ability and reuse.